Sine Qua Nons of sustainable biofuels: Distilling implications of under-performance for national biofuel programs. (September 2017) - German, Laura; Goetz, Ariane; Searchinger, Tim; Oliveira, Gustavo de L.T.; Tomei, Julia; Hunsberger, Carol; Weigelt, Jes
Abstract: Biofuels have been promoted worldwide under the assumption that they can support several strategic policy goals, while mitigating associated risks. Drawing on published evidence on performance, contributing papers to this Special Section question assumptions commonly attributed to biofuels: their carbon neutrality, their positive effect on rural livelihoods, and policymakers' ability to effectively govern for sustainability. This paper takes these findings as its starting point and asks, "What next?" for countries wishing to advance biofuels as one option for the necessary divestment from fossil fuels. Deriving recommendations for national biofuel programs from past performance is no easy task. Context, complexity, power dynamics and scaling pose significant challenges to achieving policy aims. We are nevertheless able to distill a set of sine qua nons (indispensables) for sustainable biofuel governance from the evidence and change management literatures. They are put forward not as recipes for success, but minimum conditions and "best bet" approaches requiring testing, deliberation, and refinement. Perhaps the most fundamental sine qua non is to pursue options that downscale global demand – as current levels of global energy consumption, if only in the transport sector, cannot be met by biomass-derived agrofuels in a way that meets social and environmental sustainability goals. Highlights: Paper explores consequences of underperformance for national biofuel programs. Paper distils sine qua nons for sustainable biofuels, based on published literature. The potential for sustainable biofuel production is far less than typically assumed. Biofuels can do little to meet current energy demand without unacceptable trade-offs. The most fundamental sine qua non is therefore to downscale global demand.